The contribution of the Polish coal mining industry to the economy of interwar Europe - Smierz, Marcin (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2019)
The article describes the importance and position of the Polish coal mining during the inter-war period in the structure of the European economy. The Polish mining industry at that time was subject to concentration processes in order to establish coal sales companies and cartel organisations for representation before government authorities and joint price setting. Regarding the source base, the basic research material was the archives stored in the State Archives in Katowice and Warsaw, supplemented by statistical data.
Keywords: Upper Silesia; history of economy; Polish industry; Polish coal mines; Polish foreign trade